The role of microenvironment in the initiation and evolution of B-cell precursor acute lymphoblastic leukemia - Garcia-Gimenez, Alicia; Richardson, Simon E. (Frontiers in Oncology, 2023)
B cell precursor acute lymphoblastic leukemia (BCP-ALL) is a malignant disorder of immature B lineage immune progenitors and is the commonest cancer in children. Despite treatment advances it remains a leading cause of death in childhood and response rates in adults remain poor. A preleukemic state predisposing children to BCP-ALL frequently arises in utero, with an incidence far higher than that of transformed leukemia, offering the potential for early intervention to prevent disease. Understanding the natural history of this disease requires an appreciation of how cell-extrinsic pressures, including microenvironment, immune surveillance and chemotherapy direct cell-intrinsic genetic and epigenetic evolution. In this review, we outline how microenvironmental factors interact with BCP-ALL at different stages of tumorigenesis and highlight emerging therapeutic avenues.